Aplikacija folkloristične teorije Stitha Thompsona na zbirko slovenskih pravljic - Blažič, Milena (Slavistična revija, 2009)
The first part of the paper presents Stith Thompson's theory of folklore and his motif-index of folk literature, containing 22 basic motifs and numerous sub-motifs. In the second part, the author applies this theory to the analysis of motifs and themes in the collection of Slovene folktales that includes over a hundred tales from Slovene folk tradition (fairy tales, folktales, fables, and legends).
Keywords: fairy tale; folk culture; ljudska kultura; ljudsko slovstvo; oral literature; pravljica; pravljice; slovensko ljudsko izročilo